Motivational career counselling and coaching : cognitive and behavioural approaches - Sheward, Steve (SAGE, 2012)
This thoroughly practical book combines cognitive and behavioural approaches with vocational counselling and coaching, providing clear, practical strategies and a wealth of materials that can be used with clients in one-to-one or group settings.